ANALISIS PERKEMBANGAN FINANSIAL KOPERASI SAWIT USAHA MANUNGGAL SERESAM KECAMATAN SEBERIDA KABUPATEN INDRAGIRI HULU - Siti Siti Khotijah; Shorea Khaswarina; Eri Sayamar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The aims to of cooperative to promote the welfare of members in particular and society in general. cooperative must have the ability to realize the business services that can enhance the added value and benefits to members and still consider to acquire the remaining good results. financial statements can be used as one of the parameters to measure the financial performance of cooperatives. Profit growth is one of the parameters used to measure the financial performance of cooperatives. The performance used in the calculation of financial performance over 5 years ago, by using the concept of calculating Economic Value Add (EVA). EVA calculation produces the positive EVA > 0 indicates the performance Kopsa UM is quite good because the rate of return that exceeds the average cost of capital, and is able to create value to investors. Keywords: Financial Performance, Economic Value Add (EVA)